Impact of water vapor on 1.51 μm ammonia absorption features used in trace gas sensing applications - Schilt, Stephane (My University, 2010)
Water-vapor-induced pressure broadening is reported for two NH3 absorption features at 6612.7 and 6596.4 cm−1 that are exploitable for gas sensing applications at atmospheric pressure. Absorption spectra of different NH3–H2O–N2 mixtures were measured at an elevated temperature of 70°C to enable high H2O concentrations to be reached. Line parameters were determined from a fitting procedure. The significantly greater values obtained for the H2O-broadening coefficients of the two lines compared to N2-broadening leads to cross-sensitivity effects in NH3 trace gas sensors based on spectroscopic techniques that are sensitive to the width of the analyzed absorption line, as is the case in a simple implementation of wavelength modulation spectroscopy or in photoacoustic spectroscopy. In such a case, cross-sensitivity results in inaccurate gas concentration retrieval when the composition of the diluting gas changes. H2O represents a potentially significant cross-sensitivity source as its concentration may be subject to large variations, especially in high-temperature applications where concentrations up to a couple of tens of percent may be encountered. In contrast to interference which can be minimized by an appropriate choice of the analyzed transitions, cross-sensitivity affects the entire spectrum of the analyte and is thus unavoidable in the mentioned type of gas sensors.